La educación terciaria, el emprendimiento empresarial y la tasa de desempleo en los Estados Unidos entre los años 2001 y 2021 - Pimentel Bernal, Paul Marcelo (2023)
Unemployment affects all countries (Mncayi and Meyer, 2022), but previous research suggests that it can be reduced by boosting entrepreneurship and boosting tertiary studies. (Baert et al., 2021; Precious and Daniel, 2022). This study aims to know the relationship between tertiary education and entrepreneurship and the unemployment rate, and is studied in the United States between 2001 and 2021 applying a multivariate analysis. The results suggest that tertiary education and Established Entrepreneurial Ownership have a positive impact, while Total Early Stage Entrepreneurial Activity has a negative impact.